TRPM7 as a Candidate Gene for Vestibular Migraine - Oh, Eun Hye; Shin, Jin-Hong; Cho, Jae Wook; Choi, Seo-Young; Choi, Kwang-Dong; Choi, Jae-Hwan (Frontiers in Neurology, 2020)
Objectives: Vestibular migraine (VM) is a common vestibular disorder, and familial aggregation of VM with autosomal-dominant inheritance has been described, which supports a genetic background. This study aimed to describe the clinical phenotype of a family with VM, and identify a candidate gene for VM. Methods: We recruited six individuals (four affected and two unaffected) from three consecutive generations of a Korean family with VM, and performed whole-exome sequencing to search for candidate genes. Results: All affected individuals presented with recurrent vertigo, headache, and nausea/vomiting that fulfilled the diagnostic criteria of VM. Two individuals also experienced transient hemiparesis or dysarthria during the episodes. The symptoms were triggered by physical or emotional stress. Interictal examinations showed uni- or bi-directional horizontal gaze-evoked nystagmus in three of the individuals. They had no causative mutations in genes causing familial hemiplegic migraine or episodic ataxia. Through whole-exome sequencing from three affected individuals, we identified a nonsense mutation c.3526C>T in TRPM7 that encodes a cation channel selective to Ca2+ and Mg2+. Conclusions: Alterations in intracellular Ca2+ and Mg2+ homeostasis by TRPM7 mutation may contribute to the development of the VM phenotype. Our result suggest that TRPM7 is a novel candidate gene for VM.